Perbedaan Pengetahuan dan Sikap Masyarakat Terhadap Pemberian Booklet dan Video Dagusibu Antibiotik - Madania Madania; Nur Rasdianah; Nur Ain Thomas; Faramita Hiola; Sri Nur'ain E. Ahmad (Journal Syifa Sciences and Clinical Research, 2022)
Inappropriate use of antibiotics is common in the world, both in the community and in the hospital environment, which can lead to antibiotic resistance. The purpose of this study was to determine the knowledge and attitudes of the community before and after being given the booklet and video of dagusibu antibiotics and to determine the differences and influence of community knowledge and attitudes towards the administration of the booklet and video of the dagusibu antibiotic in Lopo Village, Batudaa Pantai Sub-District, Gorontalo Regency. This research applied a quasi-experimental design with the provision of booklets and videos before and after being given education. The number of samples was 74 which were taken using non-probability sampling technique. Research data were analyzed using Wilcoxon test and Man-Whitney test. The results showed that most of the community's knowledge before being given education was still in the sufficient category (57% booklet and 62% video), and the community's attitude was in the negative category (73% booklet and 84% percent video). Meanwhile, after being given education, the community's knowledge had increased to a good category (72% booklet and 86% videos), and community's attitudes had increased to a positive category (93% booklets and videos 98%) as well. Therefore, it can be concluded that there was a significant effect on increasing knowledge and attitude after being given booklets and videos (P0.1), and there was no significant difference between giving booklets and videos on increasing community’s knowledge and attitudes (P0.1).